The Influence of Job Satisfaction, Organizational Commitment, and Organizational Culture on the Performance of Soldiers at Kodam IV/Diponegoro - Mohammad Zainollah; Ferikawita Magdalena Sembiring (Komando (Kompetensi Manajemen dan Organisasi): Bisnis dan Pertahanan, 2025)
Performance reflects the outcomes achieved by an organization within a certain period and is closely linked to the performance of its members. To improve member performance, it is important to identify influencing factors such as job satisfaction, organizational commitment, and organizational culture. This quantitative study examines the impact of these factors on the performance of Kodam IV/Diponegoro soldiers, both partially and simultaneously. The study involved 78 respondents selected using the Slovin formula, with data collected through library and field research, and analyzed using SPSS version 25.0. The results show that job satisfaction and organizational commitment do not significantly affect performance, while organizational culture does. A stronger organizational culture is associated with better soldier performance.